5-YEAR CLINICAL RESULTS OF 1073 PATIENTS WITH VARICOSE VEINS TREATED USING RADIOFREQUENCY ABLATION, ENDOVENOUS LASER ABLATION AND CYANOACRYLATE EMBOLISATION - Atik, Cem; Ozcalişkan , Ozerdem; Atik , Derya (Sanamed, 2023)
Background: There is little research on the long-term outcomes of radiofrequency ablation, endovenous laser ablation, and cyanoacrylate embolization. This study retrospectively examined the clinical results of radiofrequency ablation, endovenous laser ablation, and cyanoacrylate embolization methods.Materials and Methods: The population of the study consisted of 1256 patients who applied to the clinic with the diagnosis of chronic venous insufficiency between the specified dates and were treated with endovenous varicose veins. Sample: 431 patients in the cyanoacrylate embolization group, 230 patients in the radiofrequency ablation group, 412 patients in the endovenous laser ablation group, a total of 1073 patients. Bilateral cyanoacrylate embolization, radiofrequency ablation, and endovenous laser ablation were not applied to the patients in the same session.Results: When the 1-year occlusion rates were examined, it was determined as 97.57%, 98.26%, and 95.59% in the endovenous laser ablation, radiofrequency ablation, and cyanoacrylate embolization groups, respectively. There was no significant difference in Venous Clinical Severity Score scores between the groups before and after the procedure. Pain, paresthesia, ecchymosis, pigmentation, induration, burn, deep vein thrombosis, and phlebitis were significantly more common in the endovenous laser ablation group.Conclusions: Complications were seen in the cyanoacrylate embolization group. Endovenous laser ablation, radiofrequency ablation, and cyanoacrylate embolization applications have similar long-term results. Therefore, cyanoacrylate embolization is recommended for chronic venous insufficiency patients who want to get rid of varicose veins and improve their quality of life.
Keywords: Radiofrequency ablation; Endovenous laser ablation; Cyanoacrylate embolization; Clinical results